Some design features of the carousel type wind turbine bidarrieus - Yershina, A.K.; Sakipova, S.E.; Manatbayev, R.K. (Eurasian Physical Technical Journal, 2019)
The article presents the results of studies to improve the vertical-axis Darrieus type wind turbine with two coaxially located rotating shafts. Some design features of the symmetrical NACA-0021 airfoil are discussed. Both moving blades streamlined area scheme is shown. The brief description of the laboratory models of the carousel type wind turbine with HBI-rotor is given. It is shown that placement of a vertical-axis wind turbine at a certain height, above the surface boundary layer, can provide opportunities to further improve its effectiveness.
Keywords: wind turbine; NACA airfoil; Darrieus; Bidarrieus; HBI-rotor; surface boundary layer